Earnings management in Malaysia : a study on effects of accounting choices / Aini Aman … [et al.] - Aman, Aini; Mohd. Iskandar, Takiah; Pourjalali, Hamid; Teruya, Jenny (Faculty of Accountancy & Accounting Research Institute (ARI), 2006)
This study examines the reasons for earnings management in Malaysia by using a sample of companies listed on the Kuala Lumpur Stock Exchange. Traditional explanatory variables for earnings management (such as size and debt-to-equity ratio), tax rate, internal financing, and ownership variables were included in the model to explain the choices of accounting accruals. The study uses data for public companies for years 1995 to 1999. Since the economic downturn (1997) and market crash (1998) years are included in the study, this research is also able to evaluate the effect of these events on earnings management. This study finds that at least two factors affect earnings management in Malaysia; size of the company, and nominee s (security brokers and investment bankers) ownership.